2018
DOI: 10.1021/acssuschemeng.8b00931
|View full text |Cite
|
Sign up to set email alerts
|

Silver Inlaid with Gold Nanoparticles: Enhanced Antibacterial Ability Coupled with the Ability to Visualize Antibacterial Efficacy

Abstract: Silver nanoparticles (Ag NPs) are widely used against bacteria, but further applications are restricted by their cytotoxicity. Their antibacterial efficiency cannot be measured because of the risk of development of multidrug resistance (MDR) with use of antibiotics. An alloy nanostructure of gold nanoparticles (Au NPs) inlaid on Ag NPs was synthesized using egg white protein (denoted here as Au–Ag NPs), exhibiting an enhanced antibacterial effect and can visually indicate the antibacterial efficacy by fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 38 publications
1
31
1
Order By: Relevance
“…It was found that the microbial cell membranes were intact in the control samples as compared to the treated ones in which the integrity of the cell have also been suggested in previous reports. 20,47 The TEM analysis also revealed that the nanocomplexes were internalized into the microbial cells due to the cell membrane distortion, suggesting the good targeting ability of the developed nanocomplexes (Figure 9). 12 2.4.2.…”
Section: Morphological Changes In the Bacterial And Fungal Cell Membr...mentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that the microbial cell membranes were intact in the control samples as compared to the treated ones in which the integrity of the cell have also been suggested in previous reports. 20,47 The TEM analysis also revealed that the nanocomplexes were internalized into the microbial cells due to the cell membrane distortion, suggesting the good targeting ability of the developed nanocomplexes (Figure 9). 12 2.4.2.…”
Section: Morphological Changes In the Bacterial And Fungal Cell Membr...mentioning
confidence: 99%
“…These data validate that KL− AuAgNCs are better antimicrobial nanoagents compared to KL−AgNCs, which might be due to the catalytic action of AuNCs in KL−AuAg NCs. 20,46 Furthermore, this may also be possible due to the synergistic effect of Ag and Au, 12 in addition to the antimicrobial effect of the lignin present in KL− AuAgNCs.…”
Section: Morphological Changes In the Bacterial And Fungal Cell Membr...mentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Compared with other nanoparticles, Au NPs are nanomaterials whose surface is easy to be directly modified, which greatly promotes the development of new antimicrobial material. [ 7 ] Free Au NPs do not have the function of antibacterial activity, but the biological activity of Au NPs can be improved by photothermal or functional modification. [ 8 ] Moreover, Au NPs of small size or surface charge are not stable enough, they are easy to accumulate and lead to a sharp drop in photothermal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ag, Au, and Pt NPs are important nanocatalysts that are used in many catalytic reactions for hydrogen purification in fuel cells, chemical synthesis, and electrocatalysis to control environmental pollution [7]. Metal NPs also have broad-spectrum antimicrobial effects due to their ultrahigh specific surface area [8].…”
Section: Introductionmentioning
confidence: 99%